Effect of Kelulut honey supplementation on bone health in male rats on high-carbohydrate high-fat diet - Sophia Ogechi Ekeuku; Chin, Kok Yong; Nur Zuliani Ramli; Khairul Anwar Zarkasi; Fairus Ahmad (University of Benin, 2021)
Purpose: To determine the effects of Kelulut honey (KH) on the bone health of rats with metabolic syndrome. Methods: Male Wistar rats were randomized into normal control and metabolic syndrome s fed with a diet enriched with carbohydrate and fat. The rats in the metabolic syndrome arm were further assigned into the negative control group and honey group supplemented orally with Kelulut honey (1g/kg) daily for eight weeks. After the rats were sacrificed, the trabecular and cortical micro-architecture of the harvested femur was analysed using X-ray micro-computed tomography, while histomorphometric method was used to determine bone cell indices. Femoral biomechanical properties were analysed using a universal mechanical tester. Results: Total cross-sectional area, osteoid surface and volume, displacement and strain reduced significantly, while eroded surface increased significantly in the rats with metabolic syndrome than the normal rats (p < 0.05). The honey group showed a significant reduction in osteoclast surface than the normal healthy control (p < 0.05). Other skeletal parameters did not show a significant intergroup difference. Conclusion: Metabolic syndrome is harmful to bone health and honey has limited effects in reversing these negative effects.